Local Government's Waste Material Management with Private Sectors- A Case Study in Kota Kinabalu City Sabah, Malaysia - Mohammad Tahir Mapa; Nordin Sakke; Aliakbar Gulasan; Abdul Khair Beddu Asis; Sangkyu Rheem (2012)
Managing the environment such as recycling activities requires cooperation from all relevant parties. The importance of recycling practices have been acknowledge to have a positive effect particularly on reducing the consumption of natural resources and energy during product manufacturing. By practicing recycling, the negative impact on the environment can be minimized According to the Ministry of Housing and Local Government, Malaysia 17,000 tons of garbage have been generated by Malaysian residents (West Malaysia) a day with an average of 0.85/kg/per capita/day. This study is conducted to provide data of recycling related issues such as distribution, composition and the main actor in the City of Kota Kinabalu. Based on the fieldwork and observations the found that there are nine companies are actively involved in waste material collection. The eight companies are found to collect all kinds of materials particularly iron and aluminum. The study also discovered that the Chinese entrepreneurs are the main key players in the 'industry'. Strategic location and reasonable price are the factors contribute the success of the company. However, competition among the company is also significant.